Sihedernyi koromban - Gorkij Iskola 1946-1956 - Papp, Gábor Zsigmond (Hungary, 2000)
The Gorky School was founded in 1945 as the Soviet elite diplomatic school. From 1947 Communist immigrants returning to Hungary also sent their children there. Among them were the sons of József Révai, Mátyás Rákosi's daughter, filmmaker Márta Mészáros, János Kende, and Pál Schiffer. The film features Géza Komoróczy, Zorán Sztevanovity, Péter Halász, dr. Éva Bán, Erzsébet Birman, György Háy, Renáta Farkas, László Garai, and Györgyné Tímár.
Keywords: Documentary films